Unusual presentation of a large GIST: a challenging diagnostic dilemma - Tumpa, Rubaiya Reza; Chowdhury, Ajmal Quader; Ali, Md Omar (Bangladesh Critical Care Journal, 2023)
Introduction: Gastrointestinal stromal tumors (GISTs) are rare neoplasms of the gastrointestinal tract associated with high rates of malignant transformation. Most GISTs present asymptomatically. They are best identified by computed tomography (CT) scan and most stain positive for CD 117 (C-Kit), CD34, and/ or DOG-1. There have been many risk stratification classifications systems which are calculated based on tumor size, mitotic rate, location and perforation. Case presentation: A 42 years old man presented with dysphagia and weight loss for 2.5 months. On examination, he was severely anaemic having a huge intra-abdominal lump. He underwent laparotomy followed by removal of tumor mass with partial left lobectomy of the Liver. Conclusion:We present a case of GIST of unusual location and presentation pattern. In general, only complete resection of tumor can lead to cure, although recurrence is common after surgery. Bangladesh Crit Care J March 2023; 11 (1): 54-60